Regulation of uterine genes during the peri‐implantation period, and its relationship to the maternal brain in gestating mice. Issue 4 (22nd March 2020) - Behura, Susanta K.; Kelleher, Andrew M.; Spencer, Thomas E.
Abstract: We conducted an integrated analysis of gene expression and chromatin structure of mouse uterus to understand the regulation of uterine‐expressed genes on gestation day 4 (GD4) during the peri‐implantation period. The genes expressed in the uterus showed a significant association ( p < .0001) with the presence of the nucleosome‐free region (open chromatin) in the 5′‐untranslated region of the genes. The majority of these upstream open chromatins harbored a common class of regulatory elements known as upstream open reading frames. We also compared the gene expression profiles between the uterus and brain which showed that specific gene pairs were expressed in a correlated manner, either positively or negatively. In addition, specific ligand/receptor genes showed coordinated patterns of expression between the uterus and brain on GD4, and the level of expression of these ligand/receptors altered significantly in the brain during late pregnancy (GD15) compared with the peri‐implantation period (GD4). Collectively, these results suggest that regulation of the uterine genes during the peri‐implantation period is likely to have a functional link with the maternal brain in pregnant mice. Abstract : Specific ligand/receptor genes are expressed in a coordinated manner between the uterus and brain on gestation day 4 (GD4), and the level of expression of these genes altered significantly in the brain as the pregnancy develops to GD15. The study suggests that regulation of the uterine‐expressed genes during the peri‐implantation period is likely to have a functional link with the maternal brain in pregnant mice.